A PSYCHOLOGICAL STUDY OF THE INFLUENCE OF VALUES ON FAMILY AND MARITAL RELATIONSHIP - Bayramova, Chinara (Health and Society, 2025)
The trends shaping modern society are marked by shifts in family values, and the swift evolution of these values presents various challenges in evaluating their significance. To comprehend these challenges, one must focus on how family values evolve and their expressions. The foundational development of an individual’s personality and social relationships occurs primarily within the family unit. New values lay the groundwork for the development of a new personality type. Emerging family models are influenced by both existing and evolving values that affect relationships between spouses. Recent evidence indicates that new trends are appearing not just within specific national or ethnic contexts, but also globally in terms of family-spouse relationships, family structure, and social functions. As a result of numerous alterations, family values are currently experiencing several transformations.